What’s so Special about Legal Translation? - Harvey, Malcolm (Meta, 2002)
AbstractThe aim of this paper is to provide an overview of the main difficulties of legal translation and discuss whether they justify claims that it is a category in its own right. It proposes a wide-ranging definition of legal translation, which calls into question some received notions about its inherent difficulties.